Integrating Authentic Tuberculosis Cases into Problem-Based Learning: A Case Study of Analytical Reasoning among Public Health Students - La Ode Asrianto; Hamka Hamka; Erma Suryani Sahabuddin; Eka Apriyanti (Al-Musannif, 2026)
This qualitative case study explored public health students’ analytical reasoning experiences during the implementation of authentic tuberculosis cases in Problem-Based Learning (PBL). The study was conducted in an undergraduate public health program in Indonesia and involved students who actively participated in tuberculosis case discussions, collaborative inquiry, and reflective learning activities. Data were collected through classroom observations, semi-structured interviews, reflective journals, and learning documents, then analyzed using thematic analysis. The findings showed that authentic tuberculosis cases encouraged students to identify core public health problems, interpret contextual factors such as stigma, overcrowding, limited health literacy, and healthcare access, and evaluate evidence-based solutions collaboratively. Four major reasoning patterns emerged: contextual understanding, evidence-based analysis, collaborative reasoning, and reflective engagement. The use of authentic cases enabled students to connect theoretical concepts with real community health conditions and strengthened their problem-solving orientation and professional awareness. The study concludes that integrating authentic tuberculosis cases into PBL is an effective strategy for fostering analytical reasoning in public health education. This approach supports deeper learning, meaningful engagement, and preparation for evidence-informed decision-making in professional public health practice.